Comparative Analysis of Business Activities of Sharia Banks and Conventional Banks: Sharia and Modern Banking Perspectives - Palison, Aan; Nurnasrina; Syahpawi (MUI Kota Pekanbaru, 2024)
This article aims to explore the distinctions between Sharia Banks and Conventional Banks, along with their respective operations. Essentially, both types of banks serve as institutions that gather funds from the public in the form of savings and then redistribute these funds back to the community through loans or other means. For individuals concerned about bank interest, Sharia banking offers an alternative by implementing a profit-sharing model to calculate returns on funds, which is deemed permissible under Islamic law. The differences between Sharia Banks and Conventional Banks lie in their legal foundations: Sharia banking is governed by Islamic sharia, which is derived from the Quran, Hadith, and Ulema Fatwa (MUI), whereas conventional banks operate under the positive laws applicable in Indonesia, including civil and criminal law. These differences present unique advantages for both types of banks and their customers.